Influence of Structural Corrective and Respiratory Exercises on Cardiorespiratory Indices of Male Children Afflicted with Kyphosis - Hasan Meamari; Maryam Koushkie Jahromi; Aliasghar Fallahi; Razieh Sheikholeslami (University of Social Welfare and Rehabilitation Sciences, 2017)
Objective Structural deformities can impair different body functions, and kyphosis is one of the most common postural deformities. It seems that kyphosis induces unfavorable effects on the respiratory system. Impairment of pulmonary function, in turn, affects spirometer indices significantly. Some previous studies have indicated a positive influence of corrective structural exercise on kyphosis. Recently, respiratory muscle exercises were considered as one of the treatment methods of pulmonary disease. The purpose of the present study was to evaluate the influence of structural corrective and respiratory exercises, for a period of six weeks, on cardiorespiratory indices of male children, afflicted with kyphosis Methods & Materials The study population included male students in the age group of 10-12 years in the city of Bandarabbas. After obtaining signed consent forms from their parents, 34 boys with kyphosis were selected using the convenience sampling method. The extent of kyphosis among the participants was measured using flexicurve. Only kyphosis cases with an angle of 40 or more were selected, assimilated, and divided into three groups. The first group underwent structural corrective exercises (n=10), the second group partook in respiratory muscle exercises (n=12), and the third group was the control group (n=12) in accordance with kyphosis level. Respiratory indices including inspiratory reserve volume (IRV), expiratory reserve volume (ERV), maximal voluntary ventilation (MVV), forced vital capacity (FVC), and forced expiratory volume in 1st second (FEV1) were measured using the spirometer, and maximal oxygen uptake (VO2max) was measured using a 20 m shuttle test before and 24 hours after the last session of exercise/training. Exercise/training was undertaken for six weeks, with three sessions per week and progressively. The findings were evaluated using SPSS software version 21. After confirming the normality of the findings with the help of the Kolmogorov–Smirnov test, analysis of covariance (ANCOVA) was used to statistically compare post-experiment variables of the three groups by controlling the possible influence of pre-experiment variables.  Results The results of the study indicated that IRV (P=0.001), ERV (P=0.001), FVC (P=0.001), and MVV (P=0.001) increased significantly in the respiratory exercise group compared with the control. Similarly, IRV (P=0.001), ERV (P=0.001), FVC (P=0.007), and MVV (P=0.001) also increased significantly in the respiratory exercise group compared with the structural corrective exercise group. But, there was no significant difference in FEV1 (P=0.126), VO2max (P=0.490), and kyphosis degree (P=0.380) between the study groups. Conclusion According to our findings, it can be concluded that there is an improvement in cardiopulmonary function indices following respiratory exercises. Keeping in mind the ease with which they can be performed and the fact they do not require special devices, it can be firmly stated that respiratory muscle exercises are more efficient than other corrective exercises during a brief intervention period (six weeks). With regard to the approved influence of structural corrective exercise in kyphosis in previous studies and its relatively inadequate influence in the present study, it seems that corrective exercises need a comparatively longer duration (probably 12 weeks) to prove effective. A limitation of this study was the lack of controlling false habits in daily physical activities and postures that could have had an influence on kyphosis. Its evaluation is recommended for future studies.